2010 5th International Symposium on Telecommunications 2010
DOI: 10.1109/istel.2010.5734119
|View full text |Cite
|
Sign up to set email alerts
|

Publishing Persian linked data; challenges and lessons learned

Abstract: This paper discusses the challenges of publishing Persian linked data based on an experience of publishing some academic data from Ferdowsi University of Mashhad dataset. By analyzing the experimental results of the project and classifying the problems, some publisher-oriented solutions are proposed to improve the quality of datasets on the web.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…To this end, our approach is based on several significant quality issues identified in already published datasets on LOD. To the extent of our experience in publishing and interlinking academic data [3,4], we found that many of the published datasets suffer from quality issues. We believe that most of these issues have roots in the deficiencies of the sources from where that data is extracted, and they can be avoided if they are identified in the initial stages of publishing.…”
Section: Our Proposed Approach For Metric Developmentmentioning
confidence: 99%
“…To this end, our approach is based on several significant quality issues identified in already published datasets on LOD. To the extent of our experience in publishing and interlinking academic data [3,4], we found that many of the published datasets suffer from quality issues. We believe that most of these issues have roots in the deficiencies of the sources from where that data is extracted, and they can be avoided if they are identified in the initial stages of publishing.…”
Section: Our Proposed Approach For Metric Developmentmentioning
confidence: 99%
“…It is computed as: (3) This metric is defined to measure the misspelling errors of the values of data type properties. To this end, we have used Lucene spell checker [22] in our implementation.…”
Section: Misspelled Property Values (Msspl_prp_vlu)mentioning
confidence: 99%
“…Although data quality is an important issue for the successful organic growth of LOD, there are only a very limited number of research initiatives that focus on data quality specifically for LOD. Based on our practical experience in publishing linked data [3] we have observed that many of the published datasets suffer from quality issues such as syntax errors, redundant instances, and incorrect/uncompleted attribute values. We believe that the assessment of data quality before publishing to the LOD cloud can help publishers filter out low-quality data based on the quality assessment results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4] challenges of publishing Persian linked data are discussed then by analyzing the experimental results of the project and classifying the problems, some publisheroriented solutions are proposed.…”
Section: Related Workmentioning
confidence: 99%